BREAST CANCER SCREENING AWARENESS AMONG TRAINEE DOCTORS OF MULTAN - AWAN, Z; TAHIR, B; AWAN, H; ASEED, N; CHOHAN, Z; TAHIR, S (Biological and Clinical Sciences Research Journal, 2023)
This Cross-sectional study was designed to determine the level of awareness of breast cancer screening and early detection techniques among trainee doctors of Multan. This research was conducted at the tertiary care hospital in Multan; from January 2019 to June 2019. The questionnaire included ten awareness questions, yielding a total score of 22 House officers/interns (HOs) and post-graduate trainees (PGRs) were included in the study. Frequencies for categorical variables, median (inter-quartile range) or mean for continuous variables, and Mann Whitney U-test as a test of significant (p<0.05) were used in SPSS for analysis.328 participants were included. The mean age was 25.5±2.5 years. Half (58.2%, n-191) were females, and a half (57.5%, n-190) were HOs. Of the PGRs, 66 were of surgery and allied, and 72 were of medicine and allied. The average awareness score was 18.3±1.9. Most (95.7%, n-314) were aware of breast cancer, and nearly two-thirds (69.8%, n-229) were aware of its screening protocols. Even though 91.2% (n-299) were aware of breast self-examination, only half (46%, n-151) knew how to perform it, a third (n-93, 28%) recommended it, and a fifth (n-63, 19%) recommended screening mammography to female patients regularly. Significantly higher median awareness scores were reported for females as compared to males (19 (3) vs. 18 (3), p-0.03), PGRs vs. HOs (19 (2.6) vs. 18 (2), p-0.02), and surgical PGRs compared to medicine PGRs (19 (2) vs. 18 (3), p-0.04).based on the results it can be concluded that the level of awareness in trainee doctors regarding breast cancer and its early detection techniques was adequate.